Incidence of Pressure Injury in Individuals With Spinal Cord Injury: A Systematic Review and Meta-analysis. Issue 3 (May 2020) - Chen, Hong-Lin; Cai, Ji-Yu; Du, Lin; Shen, Hong-Wu; Yu, Hai-Rong; Song, Yi-Ping; Zha, Man-Li
Abstract : PURPOSE: The purpose of this systematic review and quantitative analysis of pooled data was to assess the global incidence of pressure injury (PI), across time frames and countries, in individuals with spinal cord injury (SCI). DESIGN: Systematic review and meta-analysis. SEARCH STRATEGY: PubMed, Web of Science, and EMBASE databases were systematically searched for studies published from database inception to January 2019, with only English language studies that reported the incidence of PIs in individuals with SCI were included. Study quality was assessed by a 14-item standardized checklist. We calculated the incidence of PIs as the number of new PIs in individuals with SCI and the total number of individuals with SCI during the study period. Findings are presented as incidence rate with 95% confidence intervals (CIs). RESULTS: The search yielded 1652 studies; after studies were reviewed for inclusion criteria, 29 studies representing N = 82, 722 patients were retained for data extraction. The global incidence of PIs was 0.23 (95% CI, 0.20-0.26). Data for regional distribution by country showed a pooled incidence of 0.43 (95% CI, 0.28-0.57) in individuals with SCI in South American countries, 0.36 (95% CI, 0.16-0.56) in African countries, 0.25 (95% CI, 0.14-0.37) in European countries, 0.23 (95% CI, 0.19-0.27) in North American countries, and 0.16 (95% CI, 0.06-0.25) in Asian countries. The incidence was 0.22 (95% CI, 0.19-0.26) in developing countries versus 0.27 (95% CI, 0.17-0.37) in developed countries. From 2000 to 2009, the incidence of PIs in individuals with SCI was 0.28 (95% CI, 0.09-0.47). The incidence rate of PIs before 2000 and after 2009 was 0.23. The hospital- and community-acquired PI incidence was 0.22 (95% CI, 0.19-0.26) and 0.26 (95% CI, 0.20-0.32), respectively. CONCLUSIONS: Study findings indicate that more than 1 in 5 individuals with SCI will develop a PI. Individuals with SCI are at high risk of developing PI, especially in community settings or low- and middle-income developing countries. The findings highlight the importance of further investigation of risk factors and prevention and management strategies for PIs in individuals with SCI.